Pengembangan Lembar Kerja Peserta Didik (LKPD) pada Materi Teks Fabel Berbasis Saintifik untuk Siswa SMP Kelas VIII - Ernawati, Yeni (Diksa : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2019)
The purpose of this study was to describe the needs of students and teachers for learning to write scientific-based fable text, produce teaching materials on Student Worksheet (LKPD) on scientific-based Fable Text material, and describe the results of expert validation of the developed LKPD. This research is a development study using a modification of the development model of Dick, Carey, and Carey and Jolly & Bolitho. The subjects of this study were students of class VIII and Indonesian Language Teachers. Data collection techniques are done using a questionnaire and documentation. The feasibility of the developed teaching material is known from the results of validation by three experts on the 4 components of teaching material, namely the component of material eligibility, language component, presentation component and graphic. Based on the results of expert validation, LKPD on the fable text material developed is categorized as good or suitable to be used as a textbook companion teaching material. In the content / material component, LKPD outlines one Basic Competency (KD) in each activity. Each activity is in accordance with the steps of the scientific approach that is equipped with worksheets and assessment rubrics so as to facilitate students and teachers in the learning and assessment process. In the language component, LKPD uses simple and effective language, and is equipped with a glossary to make it easier for students to understand new vocabulary. In the presentation and graphic components, LKPD uses larger types and font sizes, and attractive designs with illustrations of colored images.